2018
DOI: 10.5204/ssj.v10i1.437
|View full text |Cite
|
Sign up to set email alerts
|

Study and Life: How first year university students use their time

Abstract: Starting university changes the way students must structure their day. This study describes the patterns of time use of 444 Australian first year students and explores differences between gender and age groups. Overall, students were studying on average four hours per day (h/day), sleeping eight h/day and meeting Australian physical activity guidelines. A sizable portion of students’ days were spent engaging in ‘non-modifiable’ activities including self-care, chores and travel. Stereotypical gender and age dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
2
12
0
2
Order By: Relevance
“…Interactive group was more satisfied with their teaching approach than the traditional group. 15 At OSATS 2, the similar trend of cumulative score was observed. Pre teaching scores were almost similar for both the groups.…”
Section: Discussionsupporting
confidence: 69%
“…Interactive group was more satisfied with their teaching approach than the traditional group. 15 At OSATS 2, the similar trend of cumulative score was observed. Pre teaching scores were almost similar for both the groups.…”
Section: Discussionsupporting
confidence: 69%
“…Undergraduate students are in a transitional phase of life that entails many changes in their daily habits. They have moved from a structured environment (school) to a relatively unstructured environment (university) [9]. This transition reduces overall PA levels [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In the Australian context, Richardson et al [25] conducted a longitudinal cohort study with a group of first-year university students to discover time use associations by gender and age group. The authors found statistically significant differences through hypothesis testing on comparisons between population groups.…”
Section: Time Use Studies By Means Of Modeling Techniquesmentioning
confidence: 99%